The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1001/jamacardio.2016.5395
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Circulating Baseline Proprotein Convertase Subtilisin Kexin Type 9 Levels and Efficacy of Evolocumab

Abstract: Regardless of baseline PCSK9 levels, the doses of evolocumab being studied in a large cardiovascular outcomes trial suppress PCSK9 levels and consistently and substantially reduce LDL-C levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Additional research is needed to determine the relationship between PCSK9 and inflammation and to determine whether circulating PCSK9 levels influence atherogenesis in HIV. A recent study in the general population showed that PCSK9 levels do not predict LDL-c response to PCSK9 inhibitors [ 36 ], suggesting that PCSK9 levels should not be used to influence PCSK9 inhibitor treatment decisions. Studies in the general population have also shown that PCSK9 inhibition reduces plaque burden [ 37 ] and major adverse cardiovascular events [ 38 ] among high-risk patients on statins; however, it is unclear the extent to which these effects are driven by LDL lowering.…”
Section: Discussionmentioning
confidence: 99%
“…Additional research is needed to determine the relationship between PCSK9 and inflammation and to determine whether circulating PCSK9 levels influence atherogenesis in HIV. A recent study in the general population showed that PCSK9 levels do not predict LDL-c response to PCSK9 inhibitors [ 36 ], suggesting that PCSK9 levels should not be used to influence PCSK9 inhibitor treatment decisions. Studies in the general population have also shown that PCSK9 inhibition reduces plaque burden [ 37 ] and major adverse cardiovascular events [ 38 ] among high-risk patients on statins; however, it is unclear the extent to which these effects are driven by LDL lowering.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of baseline PCSK9 on reductions in LDL-C were evaluated using pooled data from four phase III randomized clinical studies [ 47 ]. Across all quartiles of baseline PCSK9 concentrations, evolocumab 140 mg Q2W and 420 mg QM suppressed circulating PCSK9 levels by 90–100% within 1 week of administration.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…The effects of PCSK9 antibodies are independent from the circulating PCSK9 concentration [38]. Apart from the therapeutic use of IgG antibodies, smaller molecular scaffolds targeting circulating PCSK9 are in development.…”
Section: Approaches To Reduce Pcsk9 Synthesis And/or Pcsk9/ldlr Intermentioning
confidence: 99%